The Effect Of Corporate Governance On Unfaithful Disclosure Designation And Unfaithful Disclosure Penalty Points - Moon, Bo Young; Park, Soo Yeon (Journal of Applied Business Research, 2017)
This paper investigates the relation between Unfaithful Disclosure Corporations (“UDC”) and corporate governance using listed firm (KOSPI and KOSDAQ) data in Korea. Prior literature reports that corporate governance has an impact on the level of disclosure and the quality of disclosure provided by companies. However, it is hard to find the studies about corporate governance and UDC at the term of disclosure quality. Compare to some financially advanced countries, Korea established corporate governance in a relatively short period of time; hence concerns have been raised the corporate governance have not played effective role to monitor management. We question how corporate governance affects companies’ unfaithful disclosure by using several corporate governance proxy variables and UDC data which is unique system in Korea.From the empirical tests, we find a negative association between the proportion of outside directors, an indicator of the board’s independence, and UDC designation, among companies listed on both KOSPI and KOSDAQ. On the other hand, there is a significant positive association between the proportion of outside directors and UDCs’ imposed and accumulated penalty points among KOSDAQ-listed companies. This implies that outside director system effectively play a monitoring role however due to different natures of members included in outside directors, the system often fails to control regarding based reasons for penalty points imposition. In addition, we find the percentage of foreign equity ownership showed statistically significant positive association with UDC designation and a significant positive association with the imposed and accumulated penalty points among KOSPI-listed companies. We interpret this results that foreign investors with a short-term investment propensity may not enough to play a proper monitoring role in Korea and thereby they cannot effectively control the disclosure quality provided by the management. We also find that there is a significant positive association between the percentage of managerial ownership and UDC designation in the KOSDAQ market.This study will contribute to academics and disclosure-related practitioners by documenting about corporate governance and its impact on unfaithful disclosure corporations.
Keywords: Corporate Governance; Outside Directors; Foreign Investors; Management Ownership; Unfaithful Disclosure Corporation